Expression of two distinct T cell receptor alpha/beta heterodimers by an antigen-specific T cell clone (The Rockefeller University Press, 1988)
A cytochrome c-specific, MHC-restricted T cell clone with two complete rearrangements of the same V beta 1 gene element was shown to express two different TCR alpha/beta heterodimers. Antipeptide antisera specific for TCR C beta 1 and C beta 2 peptides each immunoprecipitated distinct disulfide-linked cell surface heterodimers. The clone was derived from immunized allogeneic chimeric mice, and displayed multiple Ia specificities, including the ability to recognize antigen in association with both I-Ek and I-Es Ia molecules, as well as alloreactivity to the I-Eb molecule. It will be important to determine whether each receptor contributes independently to the overall specificity of the clone.